Reinventing tourism cities: Examining technologies, applications, and city branding in leading smart cities - Mehmet Yavuz; Muhittin Cavusoglu; Abdulkadir Corbaci (Journal of Global Business Insights, 2018)
Cities have become engines of economic development. Numerous cities have positively affected the living conditions of residents and visitors by using technological and innovative service delivery tools called smart city technologies and applications. These technologies and applications can be seen at government and private buildings, city facilities, information and communication technology infrastructure, and personal services. They have a net-positive impact on the environment and natural resources by reducing harmful emissions and the excessive and unnecessary use of energy, water, gas, public and private transport vehicles, and more. Cities have used these technologies and applications to brand themselves as having efficient, sustainable, and powerful economies, security, tidiness, planning of urban facilities, enhanced civic imagery, and a high quality of life. This branding, in turn, makes a city more attractive to target audiences. In this paper, smart city technologies and applications in the world’s leading smart cities were examined. Thereafter, common and city-specific applications were listed. Finally, suggestions were put forward for tourism cities to realize sustainable economic development by means of tourism and become attractive destinations for existing and prospective visitors.